Sphenopalatine ganglion block for postdural puncture headache in ambulatory setting - Cardoso,José Miguel (2017)
Abstract Background and objectives: Postdural puncture headache (PDPH) is a common complication following subarachnoid blockade and its incidence varies with the size of the needle used and the needle design. Suportive therapy is the usual initial approach. Epidural blood patch (EBP) is the gold-standard when supportive therapy fails but has significant risks associated. Sphenopalatine ganglion block (SPGB) may be a safer alternative. Case report: We observed a 41 year-old female patient presenting with PDPH after a subarachnoid blockade a week before. We administrated 1 l of crystalloids, Dexamethasone 4 mg, parecoxib 40 mg, acetaminophen 1 g and caffeine 500 mg without significant relief after 2 hours. We performed a bilateral SPGB with a cotton-tipped applicator saturated with 0.5% Levobupivacaine under standard ASA monitoring. Symptoms relief was reported 5 minutes after the block. The patient was monitored for an hour after which she was discharged and prescribed acetaminophen 1 g and ibuprofen 400 mg every 8 hours for the following 2 days. She was contacted on the next day and again after a week reporting no pain in both situation. Conclusions: SPGB may attenuate cerebral vasodilation induced by parasympathetic stimulation transmitted through neurons that have synapses in the sphenopalatine ganglion. This would be in agreement with the Monro-Kellie concept and would explain why caffeine and sumatriptan can have some effect in the treatment of PDPH. Apparently, SPGB has a faster onset than EBP with better safety profile. We suggest that patients presenting with PDPH should be considered primarily for SPGB. Patients may have a rescue EBP if needed.